Detecting malware based on expired command-and-control traffic. (July 2017) - Zou, Futai; Zhang, Siyu; Li, Linsen; Pan, Li; Li, Jianhua
In this article, we analyze the behavioral characteristics of domain name service queries produced by programs and then design an algorithm to detect malware with expired command-and-control domains based on the key feature of domain name service traffic, that is, repeatedly querying domain with a fixed interval. In total, 3027 malware command-and-control domains in the network traffic of Shanghai Jiao Tong University, affecting 249 hosts, were successfully detected, with a high precision of 92.0%. This algorithm can find those malware with expired command-and-control domains that are usually ignored by current research and would have important value for eliminating network security risks and improving network security environment.